The Influence of Using Travel Miniature Media through the Problem-Based Learning (PBL) Model and Teaching at the Right Level (TaRL) Approach on Mathematics Learning Outcomes of Grade 5 Elementary School Students - Sandi Budiana; Dwi Rahayu; Ni'matul Jannah; Arief Rahman Efendy (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Few studies have combined Problem-Based Learning (PBL) and Teaching at the Right Level (TaRL) to enhance elementary students' understanding of geometric concepts. Conventional teacher-centered instruction often limits students' active engagement, particularly in abstract mathematics topics such as the perimeter of plane figures. This study aimed to investigate the impact of integrating miniature journey media with Problem-Based Learning (PBL) and Teaching at The Right Level (TaRL) on mathematics learning outcomes. A pre-experimental one-group pre-test/post-test design was used, involving 22 fifth-grade students at SDN Layungsari 2 in Indonesia. Students completed a pre-test, received instruction using the intervention, and then completed a post-test. The assessment instrument included two descriptive items adjusted to students' ability levels. The data were analyzed using descriptive statistics and a paired samples t-test. Normality was confirmed via the Shapiro–Wilk test. The results indicated a statistically significant improvement in scores from the pre-test (M = 41.64, SD = 12.4) to the post-test (M = 64.59, SD = 14.2), t(21) = 3.94, p = .001, with a moderate effect size (d = 0.70). These findings suggest that combining miniature journey media with PBL and TaRL can support students' learning of perimeter concepts. Further research with control groups and larger samples is recommended to validate and extend these findings.